REGULATING THE PSYCHOSOMATIC HEART RATE DISORDERS THROUGH THE USE OF ANTI-STRESS MASSAGE - Doina MÂRZA-DĂNILĂ; Dănuţ Nicu MÂRZA-DĂNILĂ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The symptoms of the so-called functional cardiovascular disorders, in which emotional factors can have an etiological importance, is diverse, comprising tachycardia, anxiety palpitations, various forms of arrhythmia and neurocirculatory asthenia. No matter the causes, they can be related to one's lifestyle, personality and one's own way of perceiving everyday stress and reacting to it. Considering that anti-stress massage can help to achieve mental and physical relaxation in subjects and change their perception of the events they experience, and through this, regulate the psychosomatic heart rate disorders, diminish chronic fatigue and depression and, as such, can help prevent the emergence of the Karōshi syndrome, 19 sessions were applied to 4 subjects, over the course of 4 months. Their results, compared to the ones from other 4 subjects, proved that anti-stress massage has helped to gradually regulate the heart rate of the subjects on which it was applied.